Finite element study of magnetohydrodynamics (MHD) and activation energy in Darcy-Forchheimer rotating flow of Casson Carreau nanofluid - Ali, Bagh (2020)
Here, a study for MHD (magnetohydrodynamic) impacts on the rotating flow of Casson Carreau nanofluids is considered. The temperature distribution is associated with thermophoresis, Brownian motion, and heat source. The diffusion of chemically reactive specie is investigated with Arrhenius activation energy. The governing equations in the 3D form are changed into dimensionless two-dimensional form with the implementation of suitable scaling transformations. The Variational finite element procedure is harnessed and coded in Matlab script to obtain the numerical solution of the coupled non-linear partial differential problem. The variation patterns of Sherwood number, Nusselt number, skin friction coefficients, velocities, concentration, and temperature functions are computed to reveal the physical nature of this examination. It is seen that higher contributions of the magnetic force, Casson fluid, and rotational fluid parameters cause a raise in the temperature like thermophoresis and Brownian motion does but also causes a slowing down in the primary as well as secondary velocities. The FEM solutions show an excellent correlation with published results. The current study has significant applications in the biomedical, modern technologies of aerospace systems, and relevance to energy systems.